Cap a una cronologia dels models teatrals de Pedrolo - Rosselló, Ramon X. (Caplletra. Revista Internacional de Filologia, 2015)
This article scans Pedrolo's dramatic oeuvre starting from the comparative analysis of story-line and thematic aspects, characters, space and time. The final ambition is to emphasize the fact that three periods may be defined: early theatrical experiments (1954-1956), central production (1957-1963) and the last plays (1966-1977), that respond to different theatrical models.